(untitled) (Texas Journal of Medical Science, 2022)
In the microbiology laboratory of the Veterinary Scientific Research Institute, 8 rabbits were divided into two groups. The first group (4 rabbits) was an experimental group, which was infected with experimental Pasteurella’s, and the second group, 4 rabbits in the control group, were not infected. From the 3rd day of the experiment, blood was collected from the auricle of all Pasteurella-infected and noninfected healthy rabbits, and blood biochemical indicators were studied. It was observed that the amount of keratin and urea increased, ALT μmol/l, AST μmol/l enzymes increased from the norm, and the decrease of Fe substance caused the decrease of the amount of hemoglobin in erythrocytes in the disease